Effect of bio-inoculants on growth and yield of betel vine (Piper betle) - Chitra, R.; Janaki, D.; Jansirani, P. (Journal of Plantation Crops, 2020)
Betel vine (Piper betel) cultivation and the consumption of betel leaves is a very traditional and widespread practice in India and many South-East Asian countries. The marginal and small farmers generally cultivate betel vine in their small holdings which provide them with a means of alternative cash earning to meet their day to day livelihood. Chewing betel leaves is an old habit of the people residing in subtropical countries. It is used in several traditional remedies for the treatment of stomach ailments, infections and as a general tonic. As betel leaf is directly chewed, there is a need to improve the leaf yield and to optimize the usage of manures for the leaf production. A study was taken up to assess the efficacy of some of the bio-inoculants in combination with inorganic fertilizers in betel vine cv. SGM 1 under an open system of deep trench method. Among the various treatments, Azospirillum @ 5 kg coupled with 100 kg each of P and K ha-1 had recorded the highest vine length (195.6 cm), more number of laterals per vine (22.3) and highest leaf yield ha-1 (44.7 lakh).